Pengendalian Persediaan Bahan Pendukung Pemasangan Batu Alam dengan Mempertimbangkan Klasifikasi FSN dan EOQ - Ardiansyah, Rudi; Yuliawati, Evi (Jurnal SENOPATI : Sustainability, Ergonomics, Optimization, and Application of Industrial Engineering, 2025)
CV. XYZ is a company that operates in the interior sector, especially natural stone design and installation services. In the development of production activities there are shortages or excess stocks of supporting materials. The aim of this research is to help CV. XYZ identifies the causes of uncontrolled stock of supporting materials and prevents potential losses due to shortages or excess stock of materials. To determine this potential, the FSN method is used to classify supporting materials. then proceed with calculating using the EOQ method to find out the company's optimal order quantity. Then use Monte Carlo simulation to forecast needs for the following year. Where the results of these calculations will be used as suggestions for improvements to reduce the potential for excess and shortage of stock in the coming year. From the results of the analysis, potential shortages and excess stock arise due to the absence of special calculations and classifications which cause inventory to be ineffective